Understanding Barriers to Human Papillomavirus Vaccination among Parents of 9–10-Year-Old Adolescents: A Qualitative Analysis - Denny Fe G. Agana-Norman; Monica Martinez Martinez; Manjushree Shanmugasundaram; Abbey B. Berenson (Vaccines, 2024)
HPV vaccination rates remain low among US adolescents, with only 54% completing the series in 2019. The vaccine is recommended at age 11–12 but can be given as early as age 9. Although it has been found that offering the vaccine earlier improves completion rates by age 13, parents remain reluctant to allow their younger children to initiate this vaccine. The purpose of this study was to better understand parental beliefs regarding receipt of the HPV vaccine among their children at ages 9–10. A 40 min phone interview was completed with 21 participants who were asked about their vaccine viewpoints. Even after receiving one-on-one education from a patient navigator, many caretakers expressed inadequate knowledge of the HPV vaccine and limited exposure to both positive and negative influences. The biggest concern was vaccine side effects, often resulting from a lack of medical understanding. Most parents were reluctant to vaccinate their children at a school-based clinic or pharmacy and believed that the government should not mandate HPV vaccination for public school attendance. Our study provides insight into parental beliefs and attitudes about HPV vaccination at age 9–10 years and barriers that need to be addressed.